Reflections on the Strong Growth of Citizen Science: An Interview with Abe Miller-Rushing - Miller-Rushing, Abraham (Maine Policy Review, 2017)
Abe Miller-Rushing shares his thoughts on the growth of citizen science, which he thinks is driven by a happy set of coincidences—developments in technology, computing, communication, and data analysis; growing interest in STEM (science, technology, engineering, math) education; growing recognition that volunteers can contribute meaningfully to science (after more than 100 years of science trending in the opposite direction, towards professionalization); and an emphasis on making science more relevant to society and translating science to action.